New Species of Wild Tomatoes (Solanum Section Lycopersicon: Solanaceae) from Northern Peru - Peralta, Iris Edith (2005)
Solanum arcanum and S. huaylasense, two new wild tomato species segregated from Solanum peruvianum sensu lato, are described and illustrated. These two new species are placed in a key with two other segregates of S. peruvianum sensu lato: S. peruvianum sensu stricto and S. corneliomulleri, and the morphologically similar species S. chilense. We also present a list of all 13 species of wild tomatoes we recognize, and their equivalent former names in Lycopersicon.